Effect of Mineral Acids (H3PO4) on Rooting Response of Aging Mung Bean (Phaseolus aureus Roxb.) Cuttings via Indole Acetic Acid Level - Ahmed Habeeb Al-Mamoori (Journal of Global Pharma Technology, 2019)
Phosphoric acid (H3PO4) effect on the rooting that is response of aging mung bean cuttings as a weak mineral acid calculated on level of Indole-3-Acetic Acid (IAA). significant increase in rooting response of aged cuttings is  shown in the data (for 3days in d/H2O) with (0.01, 0.001, 0.0001%,) of H3PO4 concentrations solution and with (% 0.01 and 0.001%) concentration show extremely significant  increase in rooting response of aged cuttings (for 3days in solution of H3PO4 ), while extremely significant decrease in rooting response compared to control (d/H2O) with  extremely concentration (0.5%) . a extremely significant increase of IAA content in hypocotyls of aged cuttings in optimum concentration of H3PO4verified by Quantitative estimation of IAA by spectrophotometric method as indicators for oxidative processes that occurrence during aging phenomenon.Keywords: Aging, IAA biosynthesis, Rooting response, Mineral acids, Macronutrients, Stem cuttings, Mung bean.